Macrophages and systems biology - Hume, David (Henry Stewart Talks, 2009)
Marker for the mononuclear phagocyte system, CSF-1R, EGFP, The MacGreen mouse, Macrophages and bone, MacBlue mice, Association of macrophages with tissue remodelling during embryonic development, Cellular systems biology, Transcriptional landscape of the mammalian genome, CAGE technology, Expression profiling, Macrophage-specific promoters and their associated biology, Biology of Gelsolin, Gelsolin-related protein, IGF-1 promoter region, THP-1: a model for cellular differentiation, PMA induces macrophage markers, Motif activity analysis
Reviewed at 2020/07/23